2011
DOI: 10.1148/radiol.11110814
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer: Evaluation of Response to Neoadjuvant Chemotherapy with 3.0-T MR Imaging

Abstract: Purpose:To assess how the molecular biomarker status of a breast cancer, including human epidermal growth factor receptor 2 (HER2), hormone receptors, and the proliferation marker Ki-67 status, affects the diagnosis at 3.0-T magnetic resonance (MR) imaging. Materials and Methods:This study was approved by the institutional review board and was HIPAA compliant. Fifty patients (age range, 28-82 years; mean age, 49 years) receiving neoadjuvant chemotherapy were monitored with 3.0-T MR imaging. The longest dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 36 publications
2
60
0
Order By: Relevance
“…No DCE-MRI study excluded patients based on receptor expression. Restricting the meta-analysis to three studies with sub-mm in plane resolution and smaller than 2-mm slice thickness (68,69,79) showed that rim enhancement also increased the chance of HER2 overexpression (pOR, 2.92; 95% CI, 1.42-6.02; P < 0.01; 2 studies; Supplementary Figs. S76-S80).…”
Section: Mri Features In Relation To Her2 Overexpression In Breast Camentioning
confidence: 99%
“…No DCE-MRI study excluded patients based on receptor expression. Restricting the meta-analysis to three studies with sub-mm in plane resolution and smaller than 2-mm slice thickness (68,69,79) showed that rim enhancement also increased the chance of HER2 overexpression (pOR, 2.92; 95% CI, 1.42-6.02; P < 0.01; 2 studies; Supplementary Figs. S76-S80).…”
Section: Mri Features In Relation To Her2 Overexpression In Breast Camentioning
confidence: 99%
“…For example, it was observed that MRI was able to predict pCR more accurately in patients having HER2-positive tumours when compared to HER2-negative tumours. In the latter case, a higher falsenegative rate was observed, especially when receiving anti-angiogenic drugs [40,45]. It was also observed that the average size discrepancy between MRI and pathology was greater in tumours demonstrating limited Ki-67 staining when compared to tumours demonstrating increased Ki-67 staining [40].…”
Section: Breast Cancer Subtypes and Chemotherapy Regimenmentioning
confidence: 96%
“…In the latter case, a higher falsenegative rate was observed, especially when receiving anti-angiogenic drugs [40,45]. It was also observed that the average size discrepancy between MRI and pathology was greater in tumours demonstrating limited Ki-67 staining when compared to tumours demonstrating increased Ki-67 staining [40]. In addition, Loo et al, concluded that response monitoring using breast MRI is accurate in patients having triple-negative or HER2-positive tumours.…”
Section: Breast Cancer Subtypes and Chemotherapy Regimenmentioning
confidence: 99%
“…4). In breast cancer, MRI and fMRI have proven to be sensitive to early therapy response [73], and FDG PET/CT is capable of predicting early response to neoadjuvant therapy [74]. The potential of integrated PET/MRI must be fully explored, since this hybrid methodology will likely play a key role in evaluating recurrence and therapy response in breast cancer patients.…”
Section: Therapy Response Assessmentmentioning
confidence: 99%